Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Jasa Transportasi Darat pada PT Krakatau Argo Logistik Banten - Mukhamad Pamungkas; R. Djayendra Dewa (Logistics and Supply Chain Insights, 2025)
The purpose of this study is to determine the effect of service quality on customer satisfaction at PT. Krakatau Argo Logistics. The research method uses quantitative methods. The study was conducted at PT. Krakatau Argo Logistik Banten from February to May 2023. Subjects and information in this case include, LS leaders, prada supervisors, employees, and service users. Data collection techniques used were by questionnaires and documentation. The collected data were then analyzed through the stages of data quality testing, classical assumption testing, hypothesis testing, and drawing conclusions. The results of this study are: 1.) The results of the analysis obtained that the Tangible variable or physical evidence did not have a significant effect on customer satisfaction. 2.) The results of the analysis obtained that the Reliability variable or reliability had a significant effect on customer satisfaction. 3.) The results of the analysis obtained that the Responsiveness variable or responsiveness had a significant effect on customer satisfaction. 4.) The results of the analysis obtained that the Assurance variable or guarantee had no effect on customer satisfaction. 5.) The results of the analysis obtained that the Empathy or responsiveness variable has a significant influence on customer satisfaction. This means that assurance can be one of the reasons. This means that Empathy can be one of the main reasons in determining customer satisfaction.